Accounting Trends and Techniques in Published Corporate Annual Reports (Book). - Cannon, Arthur M.; Brush, Lauren F. (The Accounting Review, 1952)
Reviews the book "Accounting Trends and Techniques in Published Corporate Annual Reports."